Pengaruh Pengetahuan Investasi, Risiko, dan Motivasi Mahasiswa/i Terhadap Minat Berinvestasi Pada Aplikasi Bibit : (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Bandar Lampung) - Habiburahman Habiburahman; Widya Puja Kesuma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study is intended to see how knowledge of investment, risk, and motivation impact on student investment interests at 2019 industry-city university economics and business students, 2020, and 2021 in Bibit applications. The kind of study used was quantitative with sample retrieval using survey data to provide a sample of 35 respondents. Data analysis techniques use description and linear regression analysis and testing of research instruments using validity and religious tests. Research shows that there is no knowledge of investment in the students' investment interest in seed applications, no risk influence on the student investment interest in seed applications, and there is a motivating influence on the student investment interest in Bibit apps.